2019
DOI: 10.3390/medicina55110730
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Low Lean Mass in Early Rheumatoid Arthritis: A Cross-Sectional Study

Abstract: Background and Objectives: The aim of the study was to evaluate body composition (BC) of rheumatoid arthritis (RA) patients at disease onset compared to population controls focusing on the associations between low lean mass and disease specific parameters, nutritional factors and physical activity. Materials and Methods: 91 patients with early rheumatoid arthritis (ERA) (72% female) and 328 control subjects (54% female) were studied. BC-lean and fat mass parameters were measured with a Lunar Prodigy Dual Energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 40 publications
0
31
2
1
Order By: Relevance
“…Glucocorticoids are partly responsible for the loss of bone mass and changes in body composition seen in several rheumatic diseases like SLE or RA 17,[19][20][21][22] . They have negative effects on BMC and are the principal cause for secondary osteoporosis 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids are partly responsible for the loss of bone mass and changes in body composition seen in several rheumatic diseases like SLE or RA 17,[19][20][21][22] . They have negative effects on BMC and are the principal cause for secondary osteoporosis 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The factors associated with sarcopenia in RA have been demonstrated in many studies ( Table 2 ). Old age [ 36 , 37 ], BMI [ 34 , 35 , 36 ], high body fat mass [ 35 , 38 ], longer disease duration [ 37 , 74 ], bone erosion [ 34 ], low hip bone mineral density [ 36 ], malnutrition [ 37 ], low protein intake [ 72 ], and joint damage [ 30 , 33 , 37 ] were all associated with sarcopenia. Acute phase reactants such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) [ 30 , 36 , 68 , 72 ], rheumatoid factor (RF) [ 26 , 30 ], and matrix metalloprotease 3 (MMP3) [ 35 ] were also associated.…”
Section: Rheumatoid Arthritis and Sarcopeniamentioning
confidence: 99%
“…In contrast, treatment of RA using glucocorticoids (GCs) seemed to exacerbate sarcopenia. It has been reported that GCs use was positively associated with low lean mass or sarcopenia in RA patients [ 38 , 72 ]. In a chronic polyarthritis mouse model, GCs treatment prevented inflammatory bone loss but significantly increased muscle wasting [ 75 ].…”
Section: Rheumatoid Arthritis and Sarcopeniamentioning
confidence: 99%
“…RA patients present several comorbidities including obesity, metabolic syndrome, and sarcopenia, probably triggered by a disbalance of proinflammatory cytokines including TNF and IL-6 among other causes [73][74][75][76][77], that will modify the circulating metabolites [78]. Several studies have investigated circulating metabolic changes related to the metabolic syndrome and obesity [79,80].…”
Section: Comorbiditiesmentioning
confidence: 99%